Development of an Intelligent Chatbot with Voice Recognition Features to Assist Users in Analyzing PDF Documents at Politeknik Indonusa Surakarta - Wijaya, Rakyan Duta; Iskandar, Dwi; Putri, Frestiany Regina (International Journal of Computer and Information System (IJCIS), 2025)
This study aims to design an intelligent chatbot system integrated with voice recognition features to assist users in efficiently and interactively analyzing the content of PDF documents. The background of this system development stems from the difficulties many users face in understanding and extracting information from complex and lengthy digital documents. Adopting a Research and Development (R&D) approach based on the ADDIE model, this study develops a system prototype that allows users to issue commands via voice or text, and then receive responses in the form of summaries, specific answers, or information retrieval from PDF files. Although still in the design stage, this study has identified key components such as the voice recognition module, natural language processing (NLP), and PDF parser. The system evaluation plan involves testing accuracy, response relevance, and user comfort through limited simulations. Planning results indicate that the system holds significant potential in supporting educational, research, and administrative activities, although it still faces technical challenges such as voice accent variations and complex document structures. With further development that considers efficiency and sustainability, this system is expected to become a smart solution for digital document management.